PMCA activity and membrane tubulin affect deformability of erythrocytes from normal and hypertensive human subjects - Monesterolo, Noelia E.; Nigra, Ayelen D.; Campetelli, Alexis N.; Santander, Verónica S.; Rivelli, Juan F.; Arce, Carlos A.; Casale, Cesar H. (Biochimica et biophysica acta, 2015)
Our previous studies demonstrated formation of a complex between acetylated tubulin and brain plasma membrane Ca2+-ATPase (PMCA), and the effect of the lipid environment on structure of this complex and on PMCA activity. Deformability of erythrocytes from hypertensive human subjects was reduced by an increase in membrane tubulin content. In the present study, we examined the regulation of PMCA activity by tubulin in normotensive and hypertensive erythrocytes, and the effect of exogenously added diacylglycerol (DAG) and phosphatidic acid (PA) on erythrocyte deformability. Some of the key findings were that: (i) PMCA was associated with tubulin in normotensive and hypertensive erythrocytes, (ii) PMCA enzyme activity was directly correlated with erythrocyte deformability, and (iii) when tubulin was present in the erythrocyte membrane, treatment with DAG or PA led to increased deformability and associated PMCA activity. Taken together, our findings indicate that PMCA activity is involved in deformability of both normotensive and hypertensive erythrocytes. This rheological property of erythrocytes is affected by acetylated tubulin and its lipid environment because both regulate PMCA activity. [Display omitted] •The erythrocyte deformability was low when PMCA was inhibited.•High deformability of erythrocytes when activated PMCA•PMCA altered activity by adding lipids or tubulin redistribution.•Tubulin and composition of lipids regulate the deformability through their effects on PMCA.